Error correcting optical mapping data - Washimkar, Darshan, author; Boucher, Christina, advisor; Pallickara, Sangmi Lee, committee member; Montgomery, Tai, committee member (Colorado State University. Libraries, 2016)
Optical Mapping is a unique system that is capable of producing high-resolution, high-throughput genomic map data that gives information about the structure of a genome (Schwartz et al., Science 1993). Recently it has been used for scaffolding contigs and assembly validation for large-scale sequencing projects — for example, the maize (Zhou et al., PLoS Genetics, 2009), goat (Dong et al., Nature Biotech. 2013), and amborella (Chamala et al., Science 2013) genomes. However, a major impediment in the use of this data is the variety and quantity of the errors in the raw optical mapping data, which are referred to as Rmaps. The challenges associated with using Rmap data—and thus, optical mapping data—is analogous to dealing with insertion and deletions in the alignment of long reads. Moreover, they are arguably harder since the data is integral and susceptible to inaccuracy. We develop cOMet to tackle error correct Rmap data, which to the best of our knowledge is the is the only non-proprietary error correction method. Our results demonstrate that cOMet has high accuracy on simulated E. coli (str. K-12 substr. MG1655) genome.
Keywords: multiple alignment; optical mapping; optical map; error correction